Evaluation of the Drug-Resistant Tuberculosis (DR-TB) management component under the National Tuberculosis Elimination Program (NTEP) in Kerala, India, 2021-22 - Raman Swathy Vaman; Madhanraj Kalyanasundaram; Malu Mohan; Narayana Pradeepa; Manoj V. Murhekar (Lung India)
Background and Objective: We evaluated the DR-TB component of the National Tuberculosis Elimination Program (NTEP) in a high-burden district in Kerala to identify the programmatic gaps, if any, in screening, diagnosis, treatment, and follow-up of notified DR-TB patients. Methods: A mixed-methods design was used, and the evaluation was performed in two steps. In the first step, we reviewed the program documents and conducted stakeholder interviews to develop a detailed description of the program design and developed a logical framework to evaluate program performance. Consequently, in the next step, we conducted programmatic data reviews, facility surveys, and in-depth interviews with key stakeholders to identify the programmatic gaps in implementation, guided by the logic framework. Results: Of the 494 microbiologically confirmed TB patients during 2021-22, 342 (69%) were tested for drug sensitivity, and 30 DR-TB patients were identified. There was no separate district DR-TB treatment center with airborne infection control facilities, and only 16% (66/422) of the various categories of staff were trained in recent guidelines. Only 30% (9/30) of DR-TB patients were provided with any psychological assessment. The favorable treatment outcome was 80% Interviews revealed poor readiness and motivation from the private sector for screening, contextual barriers in human resource availability, transportation, and financial barriers to the beneficiary despite providing financial benefits. Conclusion: Prioritizing the establishment of a district DR-TB treatment center and sputum transport mechanism, posting a clinical psychologist dedicated to counseling patients on therapy, and training all categories of staff on DR-TB management guidelines will significantly contribute to improving program outcomes.